2013
DOI: 10.3892/ijo.2013.1997
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of anti-androgens and tegafur-uracil combination therapy for castration-resistant prostate cancer: Results of a multi-center randomized phase II study

Abstract: We conducted this study to determine whether substitution with anti-androgen (SOA) and tegafur-uracil (a pro‑drug of 5-FU) combination therapy is more effective than SOA alone after relapse from initial hormonal therapy. Patients who were histologically confirmed and relapsed after initial hormonal therapy were included. All patients were randomly allocated into two groups: SOA alone (group A) or SOA combined with tegafur-uracil (group B). The mRNA expression of four enzymes, including thymidylate synthase (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In this study, we reported that neoadjuvant LHRH antagonist and UFT combination therapy for high-risk PCa was similar to the BCR of low- and intermediate-risk PCa in patients who underwent RARP. Selecting UFT as a neoadjuvant treatment for high-risk PCa was based on the results of subsequent clinical studies [ 22 , 23 , 24 ]. Takahashi et al [ 22 ] conducted a multicenter prospective randomized phase II trial to evaluate the efficacy and safety of ADT + UFT versus ADT alone for CRPC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we reported that neoadjuvant LHRH antagonist and UFT combination therapy for high-risk PCa was similar to the BCR of low- and intermediate-risk PCa in patients who underwent RARP. Selecting UFT as a neoadjuvant treatment for high-risk PCa was based on the results of subsequent clinical studies [ 22 , 23 , 24 ]. Takahashi et al [ 22 ] conducted a multicenter prospective randomized phase II trial to evaluate the efficacy and safety of ADT + UFT versus ADT alone for CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…Tegafur-uracil (UFT) is an oral cytotoxic prodrug of 5-fluorouracil (5-FU) that contains tegafur and uracil in a 1:4 molar ratio [ 22 , 23 ]. Tegafur is metabolized in the liver to 5-FU, and uracil prevents 5-FU degeneration [ 22 ]. Adjuvant chemotherapy with UFT has been demonstrated to be effective against several types of cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations